(untitled) (Modern education and development, 2025)
This paper investigates the effectiveness of interactive teaching methods in enhancing students’ understanding of English verb tenses. It addresses the challenges learners face in mastering the complex system of tenses and argues for a more dynamic, participatory approach to instruction. The article examines various interactive strategies, including games, storytelling, role-playing, and technology-based activities, to promote active engagement and deeper understanding. It also explores the role of visual aids and contextualized examples to facilitate comprehension. By emphasizing student-centered learning, this paper advocates for the integration of interactive methods in teaching English verb tenses to improve learning outcomes and enhance communication skills.